Trained and untrained males show reliable salivary testosterone responses to a physical stimulus, but not a psychological stimulus - Crewther, B. T.; Kilduff, L. P.; Cook, C. J. (Journal of Endocrinological Investigation, 2014)
Background The testosterone (T) responses to a physical stimulus are thought to be more stable and reproducible compared to a psychological stimulus. Purpose This study compared the salivary T (Sal-T) responses to both stimuli in four groups of men: professional rugby players (n = 17), recreational rugby players (n = 10), a mixed athlete group (n = 14) and untrained controls (n = 12). Methods Each group completed three treatments: (1) watching a video with aggressive rugby footage, (2) performing a short bout of sprint exercise and (3) a control session. Saliva samples were taken before and 15 min after each treatment. Results The sprint exercise changes in Sal-T levels were similar in the elite rugby (17.1 +/- 11.1 %), recreational rugby (11.9 +/- 15.9 %), mixed athlete (27.6 +/- 32.0 %) and control groups (25.3 +/- 23.6 %). In response to the video, Sal-T increased in the elite rugby (6.9 +/- 6.4 %) and untrained groups (11.9 +/- 13.5 %), but decreased in the recreational rugby players (-7.5 +/- 11.0 %). The individual Sal-T responses to the sprints were also correlated (r = 0.69 to 0.82) with other treatment responses. Conclusions Sprint exercise had a more consistent effect on Sal-T than a video with aggressive content and thus, could provide a reliable stimulus for increasing T availability in men with different training backgrounds. Individual Sal-T reactivity also appears to be somewhat stable across different treatments. These data provide further understanding around the induction, moderation and interpretation of T physiology.